Motivasi Kinerja Karyawan UMKM Seblak Sadang Cabang Kosambi Ditengah Pandemi Virus Covid-19 - Rostiani R; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi; Pratiwi Anastasya Putri (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This observation intends to find out how the Seblak Sadang UMKM Kosambi Branch in Karawang Regency is dealing with the Covid-19 pandemic. Direct interviews with informants, especially workers at the UMKM Seblak Sadang Karawang branch of the Kosambi branch were carried out in this observation as part of a qualitative approach method. Based on the results of observations it is known that work discipline and motivation affect employee performance. Employees take responsibility for their jobs and are driven by the sense of appreciation they receive. There are goals to be achieved, the desire to achieve and receive bonuses, the existence of regulations that are flexible and not restrictive so that employees are motivated, and there are many other factors that have an impact on employee performance. Based on the Seblak Sadang UMKM Observations, the conclusions drawn are that it is better to apply an appraisal system in employee performance carried out individually with the main points of work evaluation standards, and always provide work motivation so that compensation can be given fairly according to work performance. Employees should further develop their performance and work productivity, and be responsible for their work so that it has a good impact on the Seblak Sadang MSMEs.